Study on the cross-flow ultrafiltration of mixtures of macromolecular organic and inorganic salts. (24th February 2022) - Xu, Tingting; Song, Jie; Xiu, Guangli
Abstract: Ultrafiltration (UF) has been widely applied to water treatment in the past few decades, but severe membrane fouling is one of the most significant obstacles for its further development. In reality, the constituents of feed water are complex, and the fouling behavior could be different from that induced by a single foulant. In this study, the membrane fouling induced by mixed organic foulant (sodium alginate, SA) and inorganic ions under various conditions were investigated. The effects of ion concentration and valence on the combined fouling as well as the rejection performance were examined. The results showed that compared to SA alone, the presence of inorganic ions could aggravate the organic fouling of UF membranes significantly. The fouling became more severe as the ion concentration increased. Also, ions with higher valence tended to exacerbate the fouling compared with monovalent ions. It was also found that the existence of inorganic ions had negligible effects on the rejection of organic molecules, however, the rejection of salts can be improved because of the organic matter. In addition, the analysis of the classic fouling models showed that the complete blocking model is the main fouling mechanism of the mixed SA and inorganic salts. HIGHLIGHTS: Investigated the membrane fouling induced by mixed organic foulant and inorganic ions under various conditions. Examined the ion concentration and valence on the membrane fouling as well as the rejection performance. The presence of inorganic ions will significantly aggravate the organic fouling of membranes. Complete pore blocking is the main fouling mechanism. Graphical Abstract